Vapor‐Based Multicomponent Coatings for Antifouling and Biofunctional Synergic Modifications. (2nd January 2014) - Tsai, Meng‐Yu; Chen, Yung‐Chih; Lin, Ting‐Ju; Hsu, Yin‐Chu; Lin, Ching‐Yu; Yuan, Ruei‐Hung; Yu, Jiashing; Teng, Ming‐Sheng; Hirtz, Michael; Chen, Mark Hung‐Chih; Chang, Chih‐Hao; Chen, Hsien‐Yeh
<x xml:space="preserve">Abstract</x> A general concept is introduced featuring an ideal multifunctional surface that can avoid fouling problems while allowing the installed groups to perform with the high efficacy and accuracy necessary for delivering cascading and spontaneous biological activities. The idea is realized by using a direct synthesis of a multicomponent coating containing the two functionalities of 4‐methyl‐propiolate and 4‐N‐maleimidomethyl that is achieved via chemical vapor deposition copolymerization on various substrates. The novel coating can simultaneously perform specific bio‐orthogonal reactions, including the azide‐alkyne click reaction and a thiol‐maleimide coupling reaction. In the study, azide‐terminated polyethylene glycols are first immobilized on the methyl propiolate groups to impart an antifouling property, while bioactivity is enabled by tethering biotinylated thiols or Cys‐Arg‐Glu‐Asp‐Val (CREDV) peptides on the maleimide groups. The induced antifouling properties and bioactivities are confirmed by quartz crystal microbalance and cell culture studies. Finally, precisely manipulated endothelial cells, namely, human umbilical vein endothelial cells and bovine arterial endothelial cells, are observed on a complex stent substrate and on confined areas of the poly(methyl methacrylate) substrates.